2022
DOI: 10.1186/s12871-022-01708-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between fluid intake and extubation failure in intensive care unit patients with negative fluid balance: a retrospective observational study

Abstract: Background Negative fluid balance (NFB) is associated with reduced extubation failure. However, whether achieving more NFB can further improve extubation outcome has not been investigated. This study aimed to investigate whether more NFB and restricted fluid intake were associated with extubation success. Methods We performed a retrospective study of adult patients with mechanical ventilation (MV) admitted to Medical Information Mart for Intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Other clinical variables such as fluid balance and heart failure, which have been associated with clinical outcomes in previous studies [35], [36], were associated with weaning in the initial univariate analysis but we found no significant association between those variables and the weaning outcome in the multivariate analysis. We believe that both fluid balance and heart failure can have an adverse impact on weaning from MV.…”
Section: Discussioncontrasting
confidence: 82%
“…Other clinical variables such as fluid balance and heart failure, which have been associated with clinical outcomes in previous studies [35], [36], were associated with weaning in the initial univariate analysis but we found no significant association between those variables and the weaning outcome in the multivariate analysis. We believe that both fluid balance and heart failure can have an adverse impact on weaning from MV.…”
Section: Discussioncontrasting
confidence: 82%
“…Our study also found that the prolonged duration of intubation > 10 days was significantly associated with extubation failure compared with a shorter MV duration. In the same way, many studies reported that longer MV stays significantly increased the risk of developing EF [ 2 , 13 , and 34 ]. Evidence depicted that considering early tracheostomy for those patients anticipated to have prolonged intubation may avert the occurrences of EF [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have found an association between a variety of predictors and extubation failure: the severity of critical illness, old-age patients, co-existing disease, positive fluid balance, and amount of airway secretions, poor cough reflexes, impaired mental status, and unstable hemodynamic parameters [ 1 , 2 , 12 17 ]. Nonetheless, conflicting results are reported depending on the studied population, weaning parameters, trained expertise, and medical resource available in the clinical setup [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%